Ranma 1/2. [Vol. 3, 4] - Takahashi, Rumiko, 1957- (Takahashi, Rumiko, 1957- Ranma 1/2 2-in-1 edition, 2014)
"One day, teenaged martial artist Ranma Saotome went on a training mission with his father and ended up taking a dive into some cursed springs at a legendary training ground in China. Now, every time he's splashed with cold water, he changes into a girl. His father, Genma, changes into a panda! What's a half-guy, half-girl to do?"--Publisher description.